(untitled) (JULACE: Journal of the University of Namibia Language Centre, 2018)
This paper is based on a case study carried out to instigate the motivation in students studying French as a foreign language in a tertiary institution, in an Anglophone country. There is general consensus among applied linguists that all learning is stimulated by motivation. The type of motivation is a determining factor in a student’s performance. This study presented a first of its kind in a Namibian context. Using Gardner’s self-determination theory, the study sought to establish motivation patterns in students of French as a foreign language; to determine the attitudes of students towards the French language, culture and its speakers; and to determine students’ objectives of learning French. Using Gardner’s theory, the concurrent mixed methods approach, a questionnaire was administered to the participants. The study revealed that the French community enjoys a positive image among students. However, a lack of exposure to Francophone speakers outside the classroom was a demotivating factor